Optimizing Business Performance; By Improving Production & Planning Policies in Plastic Manufacturing. - Keswani, Nikhil (2007)
Highly competitive market conditions are the driving force behind corporations achieving world-class performance levels in efficiencies and effectiveness. The quest for market share and higher revenues force organizations all around the world to revise their operating systems and functions to achieve leadership positions not only by producing quality products and services but also by introducing effectiveness and efficiencies in their operations. This study looks at two plastic manufacturing companies operating in a highly uncertain environment as case studies. This study attempts to benchmark them against each other to illustrate and analyze the core steps and decision making approach involved in the planning and control of their production processes and operations. The concepts tested revolve around the fundamentals of Lean manufacturing and related techniques, to understand and appreciate the difficulties these companies face in the day-to-day operations of their businesses. The analysis demonstrates how these two companies apply the fundamentals of Lean manufacturing principles to their operations and also points out the various difficulties they face in its application due to their circumstances and their difficult business environment. Based on the analysis and findings, these two companies were offered suggestions / recommendations that could significantly re-vamp their operating functions allowing them to gain greater competitive edge in the market place, in the industries they operate in.